Printed photonic elements: nanoimprinting and beyond. Issue 23 (12th May 2016) - Zhang, Cheng; Subbaraman, Harish; Li, Qiaochu; Pan, Zeyu; Ok, Jong G.; Ling, Tao; Chung, Chi-Jui; Zhang, Xingyu; Lin, Xiaohui; Chen, Ray T.; Guo, L. Jay
Abstract : In order to manufacture large-scale photonic devices of various dimensions at a low cost, a number of printing-based patterning techniques have been developed. Abstract : In order to manufacture large-scale photonic devices of various dimensions at a low cost, a number of patterning techniques have been developed. Nanoimprint lithography is among the most promising given its unique advantages, such as high resolution, fast processing speed, high throughput, compatibility with diverse materials, and low cost. This review covers various aspects of nanoimprint lithography, including its operational principles, material requirements, and different ways of implementation. Nanoimprint lithography facilitates numerous high-performance and low-cost photonic elements, including optical interconnects, sensors, solar cells, and metamaterials. In addition, other related patterning techniques, together with their utilization for photonic device fabrication and their integration with nanoimprint lithography, are briefly discussed.